The Role of Presumed Head and Neck Injuries in Emotion Dysregulation Among Community Women With a History of Physical Intimate Partner Violence - Fryc, Aleksandra M. (Violence against women, 2022)
Intimate partner violence (IPV) is prevalent among women and associated with negative outcomes, including emotion dysregulation. Limited research has examined factors that contribute to emotion dysregulation in this population. This study explores the potential influence of presumed head and neck injuries from IPV on five dimensions of emotion dysregulation. Participants were 352 community women who responded to an online survey. Results of a path analysis indicated that presumed head and neck injuries from IPV were significantly associated with lack of emotional clarity and difficulties engaging in goal-directed behaviors when experiencing emotions. Findings suggest an association between presumed head and neck injuries from IPV and emotion dysregulation, underscoring the potential need for considering both neurological and psychological factors in the assessment and treatment of emotion dysregulation in this population.